2022
DOI: 10.1186/s10194-022-01424-w
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide-targeting drugs and Raynaud’s phenomenon: a real-world potential safety signal from the WHO pharmacovigilance database

Abstract: Background Migraine is responsible for significant disability and societal burden. Recently, drugs targeting the calcitonin gene-related peptide (CGRP) pathway raised new hopes. CGRP, a potent vasodilator, plays a key role in the pathogenesis of migraine attacks. The deficiency of CGRP is involved in Raynaud’s phenomenon, which consists of abnormal vasoconstriction of the digits. We aimed to assess the potential association of Raynaud’s phenomenon with CGRP-targeting drugs, analyzing real-world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…Therefore, while anti-CGRP drugs can reduce the release of CGRP and relieve migraine attacks, they also can induce Raynaud’s phenomenon in some cases. A real-world study showed that anti-CGRP drugs could induce or aggravate Raynaud’s phenomenon with a significantly stronger signal than triphenylamine, which is a migraine drug that can induce the Raynaud phenomenon ( Gerard et al, 2022 ). Although the Raynaud phenomenon was rare and the use of anti-CGRP mAbs in patients with the Raynaud phenomenon had a low incidence of microvascular complications, this was still considered worthy of attention in clinical practice ( Breen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, while anti-CGRP drugs can reduce the release of CGRP and relieve migraine attacks, they also can induce Raynaud’s phenomenon in some cases. A real-world study showed that anti-CGRP drugs could induce or aggravate Raynaud’s phenomenon with a significantly stronger signal than triphenylamine, which is a migraine drug that can induce the Raynaud phenomenon ( Gerard et al, 2022 ). Although the Raynaud phenomenon was rare and the use of anti-CGRP mAbs in patients with the Raynaud phenomenon had a low incidence of microvascular complications, this was still considered worthy of attention in clinical practice ( Breen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patient imaging suggested a vasospasm mechanism and erenumab was suspected in the absence of any other evident etiologies 12 . Recent study‐based pharmacovigilance data from the World Health Organization (VigiBase®) warned about vascular safety owing to a significant disproportionality signal of Raynaud's phenomenon with CGRP‐targeting drugs, especially erenumab 13 . However, the safety profile of CGRP‐mabs could be different for molecules that target the CGRP receptor or ligand.…”
Section: Discussionmentioning
confidence: 99%
“…12 Recent study-based pharmacovigilance data from the World Health Organization (VigiBase®) warned about vascular safety owing to a significant disproportionality signal of Raynaud's phenomenon with CGRP-targeting drugs, especially erenumab. 13 However, the safety profile of CGRP-mabs could be different for molecules that target the CGRP receptor or ligand. Such is the case for the risk of hypertension, which has been related only with erenumab.…”
Section: Discussionmentioning
confidence: 99%
“…-Enfermedad coronaria o ictus reciente e hipertensión arterial sin control adecuado. -Antecedentes de fenómeno de Raynaud, especialmente cuando es secundario 58 . -Historia de estreñimiento grave y uso de erenumab 59 .…”
Section: Precauciones Contraindicaciones Y Uso En Situaciones Especialesunclassified